CNSC-23. NEURONAL ORIGIN INFLUENCES SPONTANEOUS NETWORK ACTIVITY IN GLIOBLASTOMA-NEURON COCULTURES. (14th November 2022) - Daniel, Andy; Krishna, Saritha; Popova, Galina; Kaur, Jasleen; Hervey-Jumper, Shawn L
Abstract: Neuronal activity is emerging as a driver of cancer initiation and proliferation. Several models have been developed to recapitulate cancer-neuron interactions within the tumor microenvironment; however, there is substantial diversity of neuronal subtypes within the murine and human cortex. Differences in the neuronal microenvironment may influence glioma cell behavior and fail to recapitulate in vivo mechanisms. Here, we investigate the electrophysiological properties of cortical neurons and activity-regulated paracrine signaling across co-culture conditions using microelectrode arrays (MEA). Cortical neurons were obtained from three conditions, (1) human prenatal tissues, (2) murine embyronic tissue (E18), and (3) murine postnatal tissue (P1.5), then co-cultured with primary patient-derived glioblastoma cultures. Neuronal activity was assessed using weighted mean firing rate (WMFR; spike rate multiplied by number of active electrodes) and network burst synchrony index. Characterization of the activity-dependent paracrine signaling was performed using proteomics. Initiation of spontaneous firing activity differed across neuronal conditions, with activity occurring earlier in postnatal P1.5 cultures (day in vitro [DIV] 7), whereas E18 and human prenatal cultures demonstrated delayed patterns of activity (DIV 14 and DIV 21, respectively). Glioblastoma cells were added on the first day of consistent spiking. All neuronal co-culture conditions demonstrated glioma-induced hyper-activity (increased WMFR), however in different patterns. E18 co-cultures exhibited glioma-induced hyperexcitability within 24 hours with a subsequent decrease in activity over 14 days with minimal synchrony. P1.5 demonstrated no glioma-induced hyper-excitability at 24 hours; however, WMFR peaked by 7 days and remained elevated through co-culture day 14 (including concurrent increase in synchrony). Human postnatal neurons demonstrated a steady and consistent increase in WMFR as early as 24 hours post co-culture and remained active through day 14 with no synchrony change. Our data suggest that careful consideration should go into selecting neuronal co-culture conditions for mechanistic studies.